A Role Model, A Leader in the Development of Nursing's Professional Identity in Turkey: Prof. Dr. Gülten Uyer - Arife Şanlıalp Zeyrek; Nazike Duruk; Nevin Kuzu Kurban (Association of Nurse Managers, 2016)
Professionalization of the nursing profession and the formation of academic staff have not been easy in Turkey. Our nurse leaders have assumed very important roles in achieving modern dimension of nursing in our country and have been pioneers in gaining a professional qualification in nursing. One of our leaders is Prof. Dr. Gülten Uyer.